2008
DOI: 10.1104/pp.108.127761
|View full text |Cite
|
Sign up to set email alerts
|

A Relaxed Specificity in Interchain Disulfide Bond Formation Characterizes the Assembly of a Low-Molecular-Weight Glutenin Subunit in the Endoplasmic Reticulum    

Abstract: Wheat (Triticum spp.) grains contain large protein polymers constituted by two main classes of polypeptides: the highmolecular-weight glutenin subunits and the low-molecular-weight glutenin subunits (LMW-GS). These polymers are among the largest protein molecules known in nature and are the main determinants of the superior technological properties of wheat flours. However, little is known about the mechanisms controlling the assembly of the different subunits and the way they are arranged in the final polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Previously, assembly of some high‐molecular‐weight glutenin subunits was studied in transgenic tobacco (Robert et al ., ; Shani et al ., ), and polymerization of a LMW‐GS from Triticum aestivum cv. Cheyenne, known as B11‐33, has also been investigated by utilizing transient expression in tobacco protoplasts (Lombardi et al ., ). Inter‐chain disulfide bonds were shown to be crucial for B11‐33 polymer formation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, assembly of some high‐molecular‐weight glutenin subunits was studied in transgenic tobacco (Robert et al ., ; Shani et al ., ), and polymerization of a LMW‐GS from Triticum aestivum cv. Cheyenne, known as B11‐33, has also been investigated by utilizing transient expression in tobacco protoplasts (Lombardi et al ., ). Inter‐chain disulfide bonds were shown to be crucial for B11‐33 polymer formation.…”
Section: Introductionmentioning
confidence: 97%
“…Inter‐chain disulfide bonds were shown to be crucial for B11‐33 polymer formation. However, rather than being governed by specific pairing between subunits, assembly appears to rely on a relaxed specificity with regard to disulfide bond formation, whereby each cysteine residue may form a disulfide bond with a variety of companion cysteines present on identical or different subunits (Lombardi et al ., ). This would drive the formation of a large number of complex glutenin polymers.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the presence of two cysteines does not seem to be a sufficient condition to influence positively the glutenin polymer growth, which is based on HMW‐GS x‐ and y‐type interactions, forming the pillar of glutenin polymers. As a further support to the hypothesis of the role of the number and position of cysteine residues, Lombardi et al demonstrated that glutenin polymer formation was affected by the mutation of specific cysteine residues in low molecular weight glutenin subunits.…”
Section: Discussionmentioning
confidence: 82%
“…The mechanisms regulating the folding and assembly of wheat gliadins and LMW glutenin subunits have been studied in heterologous in vitro systems by several groups Altschuler and Galili, 1994;Lombardi et al, 2009;Rosenberg et al, 1993). While the results of these studies seem to suggest a role for interactions of BiP and PDI in the processing of these prolamins, the exact nature of these interactions remains poorly understood.…”
Section: The Synthesis and Processing Of Prolamins Occur In The Ermentioning
confidence: 97%
“…However, more recent studies (Francin-Allami et al, 2011) carried out in tobacco cells have shown that tandem repeats are not the only sequences involved in ER retention of g-gliadin since both the isolated repetitive N-terminal and the cysteine-rich C-terminal domains of the protein were able to be retained and accumulated as protein body-like structures. Structural features within a LMW-GS have been suggested to determine the retention of this protein in the ER of tobacco protoplasts (Lombardi et al, 2009), while its non-repetitive Cterminal domain, in particular, has been implicated in its retention in Xenopus oocytes (Altschuler and Galili, 1994).…”
Section: Sorting Of Prolamins To the Vacuole: Different Working Hypotmentioning
confidence: 98%